MMS exposure promotes increased MtDNA mutagenesis in the presence of replication-defective disease-associated DNA polymerase γ variants. - Jeffrey D Stumpf; William C Copeland (PLoS Genetics)
Mitochondrial DNA (mtDNA) encodes proteins essential for ATP production. Mutant variants of the mtDNA polymerase cause mutagenesis that contributes to aging, genetic diseases, and sensitivity to environmental agents. We interrogated mtDNA replication in Saccharomyces cerevisiae strains with disease-associated mutations affecting conserved regions of the mtDNA polymerase, Mip1, in the presence of the wild type Mip1. Mutant frequency arising from mtDNA base substitutions that confer erythromycin resistance and deletions between 21-nucleotide direct repeats was determined. Previously, increased mutagenesis was observed in strains encoding mutant variants that were insufficient to maintain mtDNA and that were not expected to reduce polymerase fidelity or exonuclease proofreading. Increased mutagenesis could be explained by mutant variants stalling the replication fork, thereby predisposing the template DNA to irreparable damage that is bypassed with poor fidelity. This hypothesis suggests that the exogenous base-alkylating agent, methyl methanesulfonate (MMS), would further increase mtDNA mutagenesis. Mitochondrial mutagenesis associated with MMS exposure was increased up to 30-fold in mip1 mutants containing disease-associated alterations that affect polymerase activity. Disrupting exonuclease activity of mutant variants was not associated with increased spontaneous mutagenesis compared with exonuclease-proficient alleles, suggesting that most or all of the mtDNA was replicated by wild type Mip1. A novel subset of C to G transversions was responsible for about half of the mutants arising after MMS exposure implicating error-prone bypass of methylated cytosines as the predominant mutational mechanism. Exposure to MMS does not disrupt exonuclease activity that suppresses deletions between 21-nucleotide direct repeats, suggesting the MMS-induce mutagenesis is not explained by inactivated exonuclease activity. Further, trace amounts of CdCl2 inhibit mtDNA replication but suppresses MMS-induced mutagenesis. These results suggest a novel mechanism wherein mutations that lead to hypermutation by DNA base-damaging agents and associate with mitochondrial disease may contribute to previously unexplained phenomena, such as the wide variation of age of disease onset and acquired mitochondrial toxicities.